Analisis Karakteristik Rumah Tangga Penerima Program Beras Sejahtera (Rastra) di Provinsi Sumatera Barat - Rizki Selviani; Muhammad Irfan (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2022)
This study aims to analyze the characteristics of the prosperous rice beneficiary households in West Sumatra in 2017. The data source used in this study is data from the 2017 Susenas data at the BPS West Sumatra Province which contains data related to household social and economic conditions. This study uses descriptive analysis, cross tabulation, and logistic regression analysis. The results of the study indicate that there are 5 variables that have an influence on prosperous rice recipients, namely education variables, housing ownership, cooking fuel, washing water sources, and area. Meanwhile the other five variables did not have a significant effec.